2008
DOI: 10.1371/journal.pgen.1000022
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans Opa1 Homologue EAT-3 Is Essential for Resistance to Free Radicals

Abstract: The C. elegans eat-3 gene encodes a mitochondrial dynamin family member homologous to Opa1 in humans and Mgm1 in yeast. We find that mutations in the C. elegans eat-3 locus cause mitochondria to fragment in agreement with the mutant phenotypes observed in yeast and mammalian cells. Electron microscopy shows that the matrices of fragmented mitochondria in eat-3 mutants are divided by inner membrane septae, suggestive of a specific defect in fusion of the mitochondrial inner membrane. In addition, we find that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 74 publications
10
108
0
Order By: Relevance
“…S8A). We also used double RNAi to test fzo-1, a gene required for mitochondrial fusion (41). In this case, fzo-1 knockdown actually enhances the GABA neuron degeneration phenotype of coq-1-deficient animals as expected for a treatment that impairs mitochondrial fusion (Fig.…”
Section: Coq-1 Knockdown-induced Cell Death Depends On the Mitochondrialmentioning
confidence: 89%
“…S8A). We also used double RNAi to test fzo-1, a gene required for mitochondrial fusion (41). In this case, fzo-1 knockdown actually enhances the GABA neuron degeneration phenotype of coq-1-deficient animals as expected for a treatment that impairs mitochondrial fusion (Fig.…”
Section: Coq-1 Knockdown-induced Cell Death Depends On the Mitochondrialmentioning
confidence: 89%
“…Their C. elegans homologs are drp-1, fzo-1, and eat-3, respectively (28)(29)(30). We examined mitochondrial morphology in the drp-1 null mutant, and found that age-dependent mitochondrial fragmentation in the drp-1 mutant was similar to that of the wild type ( Fig.…”
Section: Drp-1-mediated Mitochondrial Defects In Activity-deficient Nmentioning
confidence: 95%
“…In C. elegans, FZO-1 and EAT-3 are required for the fusion of the outer mitochondrial membrane and the inner mitochondrial membrane, respectively (7,(10)(11)(12)(13). To determine whether mitochondrial hyperfusion induced by mma-1(RNAi) is dependent on these GTPases, we performed RNAi experiments in animals carrying a null-mutation in the fzo-1 gene [fzo-1(tm1133)] or the eat-3 gene [eat-3(tm1107)].…”
Section: Reducing Complex IV But Not Complex I Assembly Induces Mitocmentioning
confidence: 99%
“…For example, mammalian Drp1 or Caenorhabditis elegans DRP-1 are required for mitochondrial fission (6,7). Conversely, mammalian Mfn1/2 and Opa1 or C. elegans FZO-1 and EAT-3 are required for the fusion of the outer and inner mitochondrial membrane, respectively (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%